Moderating Effects of Age on Employer Brand Dimensions in Increasing Job Satisfaction - Gregory Michael Berces (ULTIMA Comm, 2023)
As it has become widely accepted that employees are the most valuable intangible assets of an organization, brand strategy has become not limited to products and services being offered, but also in recruiting high potential candidates and retaining fit employees in the company. The study aims to empirically test the influence of employee brand dimensions on job satisfaction, formulated in the study of Karnica Tanwar and Asha Prasad, in a continuing education center in Manila. Employer brand dimensions includes training and development, reputation, diversity, organization culture, work-life balance, and ethics & CSR. The result shows that the employer brand dimensions, collectively, significantly confirms the influence employee job satisfaction among employees; and age has influence as moderating variable employer brand dimensions and employee job satisfaction